The Role of Reproductive Modes in Shaping Genetic Diversity in Polyploids: A Comparative Study of Selfing, Outcrossing, and Apomictic Paspalum Species - Reutemann, Verena; Schedler, Mara; Hojsgaard, Diego H.; Brugnoli, Elsa Andrea; Zilli, Alex Leonel; Acuña, Carlos Alberto; Honfi, Ana I.; Martínez, Eric Javier (MDPI, 2025)
Exploring the genetic diversity and reproductive strategies of Paspalum species is essential for advancing forage grass improvement. We compared morpho-phenological, molecular, and genotypic variation in five tetraploid Paspalum species with contrasting mating systems and reproductive modes. Contrary to previous findings, selfing (Paspalum regnellii and P. urvillei) and outcrossing (P. durifolium and P. ionanthum) species exhibited similar phenotypic diversity patterns, with low intrapopulation variability and no morphological differentiation among populations. The apomictic species (P. intermedium) exhibited low intrapopulation phenotypic variation but high population differentiation, indicative of genetic drift and local adaptation. Outcrossing species showed greater intrapopulation genotypic variation than selfing species, which displayed a high population structure due to restricted pollen migration. The apomictic species exhibited the lowest intrapopulation molecular diversity, forming uniclonal populations with high interpopulation differentiation, highlighting the fixation of distinct gene pools via apomixis. This is the first report about genetic diversity in populations of sexual allopolyploid species of Paspalum. Population structure in these allotetraploid Paspalum species is primarily shaped by how reproductive modes, mating systems, and geographic distribution influence gene flow via pollen and seeds. Our findings contribute significantly to the conservation and genetic improvement of forage grasses, particularly for developing cultivars with enhanced adaptability and productivity.